Hukum Kausalitas antara Al-Ghazali dan Ibn Rusyd - Burhanuddin, Nunu (TAJDID, 2016)
The anomaly in the intellectualism of classic Islam has dragged the main exponent of Sunni, Abu Hamid Al-Ghazali who is against the principles of science, into an argument. The stigma appears because he is considered to have criticized the theory of causalities as tradition apart. Although this doesn't weaken the role of the human mind, we are cautioned that this critic can ruin the scientific foundation. The intense debate comes up from this because Al-Ghazali proved that he was still in agreement with “the principle that nothing can happen without n cause”, that is the adage of Ibn Rusyd,  a Muslim philosopher from Cordova. The later philosopher then criticized AI-Ghazali, otherwise known as Hujattul Islam by giving different characters on the elements of physics like fire, cotton etc. If the water and the fire have no specific characteristic so it is nonsense God creates water and fire, because eventually those materials are not slightly different. If in the nature there is no specific mechanism, so there is no specific characteristic. This is a step forward that legitimizes causality as the primary relation and not the common relation. The writer of this paper would like to emphasize something unspeakable when AI-Ghazali limits absolutisms of the cause but does not refuse the cause. It is surely unavoidable that Ibn-Rusyd, the philosopher from Cordova conveys an impression that he goes to war without fighting.